The Roles of Corporate Governance Towards Value-Oriented Islamic Finance Practices - Hasan, Z. (Universiti Sains Islam Malaysia, 2024)
This paper argues that while significant concerns have been invoked on the material aspects of Islamic finance such as financial growth and products sophistication, it is nevertheless observed that equal emphasizes have not been given on social objectives of Islamic Financial Institutions (IFIs) as part of its value-oriented frameworks. In the absence of extensive discourse on corporate governance and its roles on CSR, this paper attempts to highlight the importance of corporate governance in stimulating the social function of IFIs within the Islamic ethical dimension paradigm. This paper aims at expanding the normative objective function of IFIs by advocating corporate social responsibility (CSR) via strengthening the corporate governance framework. Unlike the western concept of corporate governance, which is based on the western business morality that derived from “secular humanist”, this paper suggests that corporate governance in IFIs is founded on the epistemological aspect of Tawhid, Shari’ah and ethics. This paper employs theoretical and case study research method to develop understanding and to advocate the notion of value oriented Islamic finance practices. The study utilizes descriptive, comparative and critical analysis approaches in extracting and analyzing the information.